The rhizosphere : Biochemistry and Organic Substances at the Soil-plant Interface - Pinton, Roberto; Ed. Varanini, Zeno; Ed (CRC Press, 2007)
"Maintaining the interdisciplinary approach of the first edition, The Rhizosphere: Biochemistry and Organic Substances at the Soil-Plant Interface, Second Edition summarizes information on soil science, agronomy, plant nutrition, plant physiology, microbiology, and biochemistry to provide a comprehensive and updated overview of the most recent advances in the field. Revised and expanded, the second edition presents new information on areas that are only recently gaining importance for understanding the complex biochemistry of the soil-microbe-plant interaction."--Jacket